Pumped-up propulsion" during front crawl swimming - Toussaint, H. M.; van den Berg, C.; Beek, W. J. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: It is currently held that propulsion in human front crawl swimming is achieved by lift and drag forces predominantly generated by the hands. Calculation of these propulsive forces relies on the quasi-steady assumption that the fluid dynamic behavior of a hand model in a flow channel (constant velocity and orientation) is similar to that of a hand of a real swimmer. However, both experimental and theoretical analyses suggest that this assumption is questionable and that unsteady and rotational propulsion mechanisms play a significant role. Theoretical considerations suggest that arm rotation could lead to a proximodistal pressure gradient, which would induce significant axial flow along the arm toward the hand. METHODS: To gain insight into such mechanisms, we used tufts to study the flow directions around the arm and hand during the front crawl, which consists of a glide, an insweep, and an outsweep phase. In a second experiment, we measured pressure during the stroke at various points along the arm and hand. RESULTS: It was observed that 1) the flow during insweep and part of the outsweep was highly unsteady; 2) the arm movements were largely rotational; 3) a clear axial flow component, not in the direction of the arm movement, was observed during insweep and outsweep; and 4) both the V-shaped "contracting" arrangement of the tufts during the outsweep and pressure recordings point to a pressure gradient along the direction of the arm during the outsweep, as predicted on theoretical grounds. CONCLUSION: Our results demonstrate the reality of the predicted rotational and unsteady effects during front crawl swimming. We hypothesize that the axial flow observed during the outsweep has a propulsion-enhancing effect by increasing the pressure difference over the hand. Further investigation is required to establish more accurately the role of axial flow on propulsion.